Modification of structure and properties of nanostructured VT1-0 titanium alloy under ultrasonic influence - Savchuk, E.S.; Sokolenko, V.I.; Karaseva, E.V.; Mats, A.V.; Frolov, V.A. (Вопросы атомной науки и техники, 2022)
The effect of ultrasonic influence on the structure evolution and creep of nanostructured titanium alloy of the grade VT1-0 obtained by the method of severe plastic deformation has been studied. It is shown that ultrasonic influence with a frequency of f = 20 kHz and an amplitude of 65 MPa leads to relaxation of internal stresses in the nanostructured VT1-0 alloy due to the formation of an equilibrium structure of boundaries without noticeable grain growth. In this case, the mechanical properties of the alloy change as follows: the tensile strength increases, while maintaining the yield strength and ductility. The reason for the observed effect may be the low stacking fault energy of the VT1-0 alloy, which complicates the course of relaxation processes, as well as the rearrangement of the structure during creep with the formation of new deformation boundaries, which are more resistant to tensile loads.